The Role of The Father as Single-Parent in Childcare - Sri Lestari; Nafila Amaliana (Universitas Negeri Malang, 2020)
Changes in the role of couple occur when the couple divorced. The father who initially served as a family breadwinner, then also did the mother's task. The purpose of this study is to understand the role of fathers as single parents in parenting. A qualitative approach was used in this study. The research data were obtained from semi-structured interviews of four fathers who cared for their children under the age of 12 years. Thematic analysis is used to find emerging themes. Data validity is achieved by the member-checking technique. The results showed that as a single parent, fathers became caregivers, motivators, mentors, study companions, and child discipline reinforcers. The family and school provide support for fathers in carrying out the role of single parents. Being a single parent is felt as a burden by fathers. Father felt uncomfortable when required to do tasks that he considered to be women's duties when outside of the house.Keywords: fathering; single-parent; role adjustment; qualitative research.